1998
DOI: 10.1002/(sici)1099-0895(199803)14:1<95::aid-dmr200>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

The intrathymic expression of insulin-related genes: implications for pathophysiology and prevention of Type 1 diabetes

Abstract: Recent experimental work has challenged and shattered the old concept of a sequestration of pancreatic islet antigens from developing T-cells within the thymic environment. There is now compelling evidence that the central immunological tolerance of the whole insulin family may be induced during the process of T-cell ontogeny in the thymus. Transcripts of insulin-like growth factor II (IGF-II), IGF-I and insulin genes have been characterized in human, rat and mouse thymuses. At the peptide level, IGF-II was sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 60 publications
0
16
0
1
Order By: Relevance
“…Though the autoimmune nature of type 1 diabetes is well established, animal experiments and human clinical studies have failed to determine the specific origin of the immunological self-reactivity against insulin-secreting islet b-cells. It has been hypothesized, however, that specific self-reactivity of the immune system may develop from a defect in the thymic establishment of central self-tolerance [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Though the autoimmune nature of type 1 diabetes is well established, animal experiments and human clinical studies have failed to determine the specific origin of the immunological self-reactivity against insulin-secreting islet b-cells. It has been hypothesized, however, that specific self-reactivity of the immune system may develop from a defect in the thymic establishment of central self-tolerance [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…It is also the case for the whole insulin family, since transcripts of insulin-like growth factor 2 (Igf2), Igf1, and insulin (Ins) genes have been characterized in human, rat, and mouse thymuses (21,22,33,34,61). At the peptide level, IGF-2 was shown to be the dominant polypeptide of the insulin family in the thymus epithelial network from different species (17,18,34).…”
mentioning
confidence: 99%
“…Igf2 transcripts were also present in the thymus from all BBDR rats, but were not detected in the thymus from more than 80% of BBDP rats, in close concordance with the incidence (86%) of autoimmune diabetes in those rats. This defect in Igf2 transcription in BBDP thymus could contribute to both their lymphopenia (including CD8+ T cells and suppressor/regulatory RT6+ T cells) and to the absence of central self-tolerance to insulin-secreting islet b cells [74,75]. Other authors have shown that susceptibility to autoimmune diabetes is correlated with the level of Ins2 transcription in the mouse thymus [76].…”
Section: Environmental Factorsmentioning
confidence: 97%